Sex-based outcomes of mitral surgery for ischaemic mitral regurgitation: protocol for a systematic review and meta-analysis - Tim Ramsay; Vincent Chan; Jodi Edwards; Pierre Voisine; Kenza Rahmouni; Nicolas Mathieu Gauthier; Navneet Kang (BMJ Open)
Introduction Patients with ischaemic mitral regurgitation (MR) have markedly increased cardiovascular mortality compared with those with primary MR. The sex-based prognosis of patients with ischaemic MR undergoing mitral surgery remains unclear. The goal of this systematic review is to evaluate long-term mortality, reoperation, heart failure rehospitalisation and MR recurrence in women who undergo mitral valve surgery for chronic ischaemic MR, compared with men.Methods and analysis The MEDLINE, EMBASE, Scopus and Cochrane Central Register of Controlled Trials databases will be searched for studies reporting surgical outcomes for ischaemic MR. Studies published before 10 June 2024 and those stratifying outcomes by sex will be included. The primary outcome of this systematic review is long-term (≥1 year) mortality following mitral surgery. Secondary outcomes include operative mortality, mitral valve reintervention, heart failure rehospitalisation and MR recurrence, as assessed by echocardiography.Risk of bias will be ascertained with the Newcastle–Ottawa scale. Heterogeneity will be assessed using Higgin’s I2 statistic. If the included studies demonstrate adequate homogeneity in their design and comparator, meta-analyses with a random-effects model will be conducted to combine estimates.Ethics and dissemination This systematic review uses data from previously published studies and does not involve interaction with human subjects or access to individual patient data. Therefore, ethical approval is not required for this study. The findings from this review will be disseminated through publication in a peer-reviewed journal and various media, including but not limited to, conferences, congresses and symposia.Trial registration number In accordance with the guidelines, our systematic review protocol was registered with the International Prospective Register of Systematic Reviews on 5 July 2024 and was last updated on 4 April 2025 (Registration number: CRD42024560892).